2008
DOI: 10.1016/j.taap.2007.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2,3,7,8-tetrachlorodibenzo-p-dioxin administration and high-fat diet on the body weight and hepatic estrogen metabolism in female C3H/HeN mice

Abstract: We studied the effect of administration of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) by i.p. injection once every two weeks in combination with a high-fat (HF) diet for 8 or 16 weeks on the body and organ weight changes as well as on the hepatic enzyme activity for estrogen metabolism in C3H/HeN female mice. Administration of TCDD at 100 μg/kg b.w. once every two weeks for 8 weeks increased the body weight by 46% in the HF diet-fed animals, but not in the regular diet-fed animals. This is the first observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Zhu et al (2008) reported that body weights of adult C3H/HeN mice exposed to 100 µg TCDD/kg body weight once every 2 weeks for 8 weeks were > 40% higher than those of control mice. This body weight change was seen only when mice were fed a high fat diet, which was not out of the range of an American diet.…”
Section: At As a Target Of Pollutantsmentioning
confidence: 99%
“…Zhu et al (2008) reported that body weights of adult C3H/HeN mice exposed to 100 µg TCDD/kg body weight once every 2 weeks for 8 weeks were > 40% higher than those of control mice. This body weight change was seen only when mice were fed a high fat diet, which was not out of the range of an American diet.…”
Section: At As a Target Of Pollutantsmentioning
confidence: 99%
“…Low dose DES exposure resulted in increased body weight in the postnatal period, while high dose exposure resulted in reduced body weight; in contrast, high dose exposure to DDT in utero led to elevated body weight, whereas lower dose exposure reduced body weight [153]. Likewise, TCDD has been shown to induce wasting at higher doses of exposure [154], while lower doses result in weight gain [155]. Whether these divergent effects result from alterations in the responsiveness of the same signal transduction cascade or represent activation/inhibition of different pathways at different concentrations requires further investigation.…”
Section: The Dose May Not Always Make the Poison: The Challenge Ofmentioning
confidence: 99%
“…The connection between dietary fat and chemical exposure was first shown in 1974 when male rats exposed to the plasticizer DEHP only exhibited augmented body weight gain and adiposity when fat was present in the diet [158]. Interestingly, exposure of mice to TCDD, most often associated with anorexigenic and wasting effects [154], results in significantly increased body weight if the animals are also fed a high-fat diet [155]. Because of the clear role that the “Western” diet plays in the obesity epidemic, understanding how EDCs interact with caloric excess to promote metabolic disruption is critical for characterizing potential synergy among the various factors that comprise an obesogenic environment.…”
Section: The Challenges Of Coordinate Stressors and Mixturesmentioning
confidence: 99%
“…Experimental studies support a link between TCDD exposure and metabolic alterations. TCDD exposure has been associated with wasting syndrome in rodents fed a normal diet (Seefeld et al 1984), and with accelerated weight gain in mice fed a high-fat diet (Zhu et al 2008). Effects on glucose homeostasis have also been reported based on in vivo and in vitro studies, including reduced glucose uptake in adipose tissue, liver, and pancreas; altered glucose tolerance; and impaired insulin secretion (Enan and Matsumura 1993; Enan et al 1992a, 1992b; Ishida et al 2005; Kurita et al 2009).…”
Section: Introductionmentioning
confidence: 99%